Studi Kasus Hipertiroid pada Laki-laki Usia 41 Tahun - Afifah Mardhatillah; Yenny Sulisma (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Hyperthyroidism is a condition characterized by elevated levels of circulating thyroid hormones due to hyperactivity of the thyroid gland, commonly caused by Graves’ disease, toxic multinodular goiter, or toxic adenoma. It is marked by increased levels of free thyroxine (fT4), thyroxine (T4), free triiodothyronine (fT3), or triiodothyronine (T3), along with suppressed levels of thyroid-stimulating hormone (TSH). In this case study, a 41-year-old male presented with an enlarging neck mass and was diagnosed with hyperthyroidism, having been on antithyroid medication for the past three months. The patient also reported palpitations, hand tremors, excessive sweating, and a 15 kg weight loss over the past three years. Based on medical history, physical examination, supporting investigations, and prior diagnosis, the patient was confirmed to have hyperthyroidism. He received appropriate treatment and was discharged after clinical improvement.